Oxide particle coarsening at temperature over 1473 K in 9CrODS steel. (December 2016) - Oono, N.; Nakamura, K.; Ukai, S.; Kaito, T.; Torimaru, T.; Kimura, A.; Hayashi, S.
Highlights: The oxide particle coarsening in a 9CrODS steel was evaluated at temperature over 1473 K. The oxide particles coarsen through Ostwald ripening. The growth rate of the oxide particles follows the fifth-power law, which is in the region of dislocation 'pipe' diffusion. The activation energy for pipe diffusion was remarkably high, 891KJ/mole, indicating that it should be affected by some other mechanisms. Abstract: The oxide particle coarsening was evaluated at temperature over 1473 K by means of transmission electron microscopy (TEM). After annealing of the 9CrODS extruded bar, the size of oxide particles increases while the number density decreases, indicating that the oxide particles coarsen through Ostwald ripening. The growth rate of the oxide particles follows the fifth-power law, which is in the region of dislocation 'pipe' diffusion. The activation energy for pipe diffusion, however, was remarkably high, derived as 891 KJ/mole. The stability of oxide particles and the difference of the diffusion velocity in between bcc- δ phase and fcc- γ phase should be considered as the contributions to the activation energy.